Pemanfaatan Media Sosial Tiktok dalam Optimalisasi Branding Produk pada UMKM Stick Ikan Sidat - Alfarisi, Muhammad Daffa'; Chilm, Ahmad Rofi; Rohmah, Uyunur; Wulandari, Alfi; Azizah, Siti Nur; Fayani, Eva Sisilia Dwi; Evelyana, Ivana Nala; Chaq, Ahmad Syuhudul; Mutafarida, Binti (Welfare : Jurnal Pengabdian Masyarakat, 2026)
This empowerment explores the use of TikTok as a digital marketing strategy to strengthen the branding of Stick Ikan Sidat, a local MSME. Using a Participatory Action Research (PAR) approach, the program involved needs assessment, training in content creation, and the application of marketing strategies. The results show significant improvements in brand awareness, proven by higher engagement, follower growth, and expanded market reach, with several videos reaching the For You Page (FYP). Despite challenges in consistency, creativity, and resources, TikTok proved to be an effective and sustainable tool for MSMEs to compete in the digital era.